Lentils and Gluten Cross Contact - Thompson, Tricia; Lyons, Trisha Bury; Keller, Amy (Frontiers in Nutrition, 2022)
Lentils are considered naturally gluten-free and are a recommended food for people with celiac disease and other gluten-related disorders. However, like oats, they appear to be at a heightened risk of cross contact with gluten-containing grains. The purpose of this study was to spot check for the presence of errant gluten-containing grains in a variety of brands of lentils purchased in 2021. Twenty-five bags of different dry lentil products representing 24 brands were purchased online and at various grocery stores. Each bag of lentils was individually hand sorted. Two of the 25 packages of lentils contained errant gluten grains. One 16-ounce bag contained a grain of wheat. Another 16-ounce bag contained a grain of wheat and a grain of barley. For a product to be considered gluten-free in the United States, it must contain less than 20 mg of gluten per kilogram (or 20 parts per million of gluten). A product at the 20-ppm level of gluten should contain no more than 2 gluten-containing grains per kilogram or 35.2 ounces of food (or 1 gluten containing grain in 17.6 ounces of food). Based on these calculations, a 16-ounce bag of lentils containing 1 gluten-containing grain would not be considered gluten-free. Lentils are at risk of cross contact with gluten-containing grain. Consumers should continue to sort through and rinse lentils before cooking.